Evaluasi Outcome-Based Education pada Mata Kuliah Al-Qawāʿid al-Asāsiyyah Menggunakan Model CIPP - Amiroh Amiroh; Aziz Muzayin; Baiq Ayu Putri Tsurayya M; Syefira P aramita Putri; Muflizan Muflizan (STIQ Amuntai, 2025)
This study aims to evaluate the implementation of Outcome-Based Education (OBE) in the Al-Qawāʿid al-Asāsiyyah course at the Arabic Language Education Study Program, Institut Agama Islam Pemalang, using the Context, Input, Process, Product (CIPP) model. A concurrent embedded mixed-methods design was employed, involving 51 students and one course lecturer as the key informant. Data were collected through document analysis, classroom observation, questionnaires, and semi-structured interviews, then analyzed using descriptive quantitative statistics complemented by interactive qualitative analysis. The results show that OBE implementation falls into the Very Good category, with an average score of 89.5%. Specifically, the context component scored 90%, input 83%, process 90%, and product 95%. These findings indicate that learning planning has been aligned with the principle of constructive alignment through the integration of Graduate Learning Outcomes (CPL), Course Learning Outcomes (CPMK), and the Semester Learning Plan (RPS); that instructional implementation was participatory and integrated with the assessment system; and that student learning outcomes were optimal. Nevertheless, the input component—particularly interactive learning media and CPMK-based assessment rubrics—remains the relatively weakest area and requires further strengthening. This study contributes theoretically by reinforcing the use of the CIPP model for evaluating OBE implementation at the course level, and practically by offering evidence-based recommendations for improving outcome-based Arabic language instruction.